Antibacterial efficiencies of Ag-Tio2(P25) catalyst under different light condition - Hoang Thi Tuyet Nhung; Doan Thi Kim Quyen; Le Thanh An (Journal of Technical Education Science, 2018)
In recent years, the applications of Ag-TiO2 nanomaterial in water purification process has gained wide attention due to its effectiveness in disinfection under UV light as well as the possibility of utilizing visible light spectrum. This paper aims to determine photocatalystic efficiencies of Ag-TiO2(P25) catalyst in disinfection under UV light, visible light and in dark. Ag-TiO2(P25) was synthesized by impregnation method with the mole percentage of Ag to TiO2 at 0.5, 1, 2, 5 and 10% in batch experiments within 30 reacting - minutes. The presence of silver in 1%Ag-TiO2(P25) nanomaterial increase the disinfection efficiencies under solar irradiation (5-log(10)) was higher than TiO2(P25) under solar irradiation (2-log) or extremely higher than under solar light ( 1-log) and in dark (0%) after 20 minutes. Under UVC illumination, strong reduction on the survival number of E.coli cells with the presence of 1%Ag-TiO2(P25). Meanwhile a combination of silver and TiO2(P25) was found to significantly increase the disinfection efficiency.